The Scope of Philosophical Conceptualisation of Music in Classical Greece - Šavėla, Šarūnas (Literatūra, 2020)
This article addresses the concept of music (μουσική), the problematics of its definition and ambiguities of its conceptual content. Here we discuss the philosophical treatises of Classical Greece, question the conflicting values attributed to the phenomenon of music, and analyse the relationship between music and text in a musical-poetical performance. Due to the very broad understanding of what music is and how it functions, the philosophical treatises discuss music both as a practice that corresponds to the divine laws of kosmos and as an activity of doubtful significance. Such opposing values attributed to musical practices render the discussion of the phenomenon in its entirety more difficult. This article proposes reconsidering the approaches towards musical thinking, musical practices, and literary texts that were followed by music, suggests to distinguish the conceptual layers based on the different meanings of the term, and to analyse these layers in a clearly defined, yet interlinked, way.